A capture of a lesser bandicoot rat Bandicota bengalensis (Rodentia, Muridae) at Callao Port, Perú: anecdotal record or potential invasive alien species? - Pacheco, Víctor (2019)
The Lesser bandicoot rat Bandicota bengalensis (Gray and Hardwicke, 1833) is a murid rodent distributed mostly in Asia that can cause substantial negative economic impact in urban and rural areas. Until now, the species has been mostly restricted to the Asian region; and no specimen has been captured or reported as a stowaway arriving to an American port. Here, I report on one specimen captured in Callao’s maritime port, Peru, during sanitary inspection surveillance, identified based on external and cranial characteristics, and similar meristic reported values. This finding shows the potential threat of this species as an invasive alien species and highlights the need for strengthening invasive species protocols on ships.